Effect of Mil-88a metal-organic framework coating on the electrochemical properties of LiCoPO4. Issue 1 (1st January 2023) - Hamdalla, Taymour A.; Aboraia, A.M.; Darwish, A.A.A.; Al-Ghamdi, S.A.; Alfadhli, S.; Soldatov, Alexander
Abstract: Towards solving the poor electrochemical performance of LiCoPO4 as a cathode in Lithium-ion batteries, here we propose a novel durable one-pot technique. Mil-88a metal-organic framework (MOF) nanoparticles have been incorporated through LiCoPO4 synthesis to form a metal-carbon layer after calcination. The structure of our novel cathode has been investigated using XRD, XRF, and TEM. The TEM images showed that the increase in the concentration of Mil-88a to 3% and annealed under air led to forming of a homogeneously distributed shell layer from porous carbon and doped with iron oxide nanoparticles (10–40 nm). The X-ray photoelectron spectra of LiCoPO4@Mil-88a verifies the presence of a Fe-rich surface layer on the nanoparticle surface of LiCoPO4 . The electrochemical studies assured that the 1st cycle yielded a discharge-specific capacity of 138 mAhg −1 . The Mil-88a MOF is a basis for metal atoms and carbon, increasing the bulk conductivity.